The challenges in managing the construction of an oil and gas platform: A case of Malaysia Marine and Heavy Engineering Sdn. Bhd. - Mohd Izwan, Mohd Din (2025)
The construction of offshore oil and gas platforms presents substantial project management and engineering challenges, particularly in emerging markets such as Malaysia, where Malaysia Marine and Heavy Engineering Sdn. Bhd. (MMHE) serves as a leading EPCIC (Engineering, Procurement, Construction, Installation, and Commissioning) contractor. This single-case study aims to explore and analyze the critical challenges MMHE faces in managing large-scale platform construction, focusing on technical complexity, financial constraints, supply chain disruptions, regulatory compliance, and human capital management. Methodologically, the study synthesizes corporate project data, including the experience of building Asia’s first deepwater truss spar at MMHE Pasir Gudang yard, Johor Malaysia, which entailed intensive technology transfer through collaboration with Technip and infrastructure upgrades such as skidding tracks and covered workshops alongside industry coverage of escalating competition compressing margins and accelerating timelines, as well as yard optimization efforts; relevant literature on workforce safety and engineering skills; and evidence of digital transformation initiatives, including AI-driven networking across its 500-acre yard to support predictive maintenance and digital workflows. Thematic coding identifies four interlinked challenge domains: (1) technical demands, including advanced fabrication techniques, continuous technology transfer, and infrastructure upgrades; (2) financial risks arising from cost overruns, volatile material pricing, and inflexible lump-sum EPCIC contract models; (3) supply-chain and logistical volatility exacerbating delivery pressures; and (4) regulatory and human capital constraints, including stringent HSE compliance and chronic shortages of skilled technical labor. The study emphasizes the necessity of deploying strategic management practices such as agile project governance, modular construction approaches, digital innovation, and proactive risk management frameworks to mitigate these challenges. Implementing these recommendations can enhance MMHE operational resilience, improve project delivery outcomes, and reinforce its competitiveness in the global offshore construction sector.